PENGARUH PENDIDIKAN KESEHATAN MEDIA VIDEO TERHADAP PENGETAHUAN MENSTRUAL HYGIENE PADA REMAJA PUTRI DI SMP NEGERI 1 PAMIJAHAN BOGOR TAHUN 2023 - Dea Novia Ramadhani; Triana Indrayani; Bunga Tiara Carolin (KHD Production, 2024)
Background: Adolescent girls’ knowledge of menstrual hygiene is very important. The consequences of poor menstrual hygiene can lead to disorders of the reproductive organs, including vaginal discharge. The incidence of vaginal discharge in Indonesia (2018) obtained data as much as 50% of adolescent girls experience vaginal discharge and increases every year. One way to improve knowledge is by providing video media health education. This study aimed to find out the influence of video media health education on menstrual hygiene health knowledge in adolescent girls. This research used a pre-experimental design with a one-group pretest-posttest design. The population was adolescent girls in grade VIII at Junior High School 1 Pamijahan Bogor with 187 students. The sample used was 65 samples obtained through stratified random sampling technique. The research instrument used a questionnaire. The analysis used was univariate and bivariate with statistical tests using the Paired Sample T Test. The univariate results of the mean knowledge of menstrual hygiene before the intervention were 62.57, and after the intervention, it was 90.45. The bivariate results show a p-value of 0.000, which means that video media health education has an influence on improving knowledge about menstrual hygiene. There is the influence of video media health education on menstrual hygiene health knowledge in adolescent girls at Junior High School 1 Pamijahan Bogor. Using video media for health education to improve knowledge about menstrual hygiene.